Effect of fluoride varnish supplemented with sodium trimetaphosphate on enamel erosion and abrasion - Manarelli, Michele Maurício [UNESP]; Moretto, Marcelo Juliano [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Martinhon, Cleide Cristina Rodrigues [UNESP]; Pessan, Juliano Pelim [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (My University, 2013)
Purpose: To assess in vitro the effect on enamel erosion ERO and erosion followed by abrasion (ERO+ABR) of varnishes with different fluoride concentrations, supplemented or not with sodium trimetaphosphate (TMP). Methods: Bovine enamel blocks were randomly divided into six groups according to the type of varnish used: placebo (no F), NaF 5%, NaF 2.5%, NaF 2.5% plus TMP 3.5%, NaF 2.5% plus TMP 5%, NaF 2.5% plus TMP 10%. Varnishes were tested for ERO and ERO+ABR, separately for 3 and 5 days. ERO was done by immersion in Sprite Zero (5 minutes, 4x/day), while ERO+ABR was performed by brushing for 15 seconds after each erosive challenge. Enamel wear (pm) and cross-sectional hardness (AKHN) were assessed after the experimental periods. Data were analyzed by ANOVA, Tukey's test and Pearson's correlation coefficient (P< 0.05). Results: Varnishes supplemented with TMP promoted significantly lower wear and hardness loss when compared to the other treatments in all conditions studied (P< 0.05). Similar wear rates were observed for the placebo, NaF 2.5% and NaF 5% varnishes (P< 0.05). Greater wear was observed after 5 days of ERO and ERO+ABR when compared with 3 days (P< 0.05). Positive and significant correlations were found between enamel wear and AKHN. No dose-response relationship was found between TMP concentration and wear and hardness. It was concluded that fluoride varnishes supplemented with TMP had a higher protective effect against ERO and ERO+ABR, which was associated with a reduction in enamel softening. (Am J Dent 2013 ;26:307-312).